CRITICAL REVIEW OF GROWTH POPULATION, PLASTIC WASTE AND THE DIGITAL SOCIETY IN INDONESIA - Pramanti, Adilita; Chotim, Erna Ermawati (Jurnal Partisipatoris, 2019)
Population growth has the potentialincreasing the generation of physical plastic waste which gives a new color to the object of environmental movement as a new social movement in the digital era where people's knowledge about waste is obtained through information on social media in a wide and varied manner. Every human being and group in society must be related to garbage. Especially when population growth is one of the factors that later becomes a critical problem. Increased Trends in the global population in the 21st century reveal an increase in rural migration to cities in the world and rapid population growth in urban centers and urban village.The emergence of business groups in various levels on social media that mainstreamed and utilized plastic waste actually triggered a new style of consumerism. With the rapid growth of consumerism the population has only switched from replacing the use of plastic products and using products that are more environmentally friendly. However, if population growth is high, easy access to consumption needs, internet access and media are not limited to productive age groups who have many necessities of life and the need for social prestige in cyberspace or everyday, new style consumerism will only find new places later. strengthen global capitalism and make the term "modern society" who care about the dangers of plastic waste to develop. The idea of selling ecotourism tickets by exchanging plastic bottles, garbage banks, green and other movements that appear every day in the media then makes pseudo-accumulated awareness for media users in BPS data (2015) Mobile phone use is in productive age so access to consumerism is a new style in the issue of plastic waste then has its own place in the development of the population as part of the capital of global capitalism. The author wants to focus on further research in order to find renewal and is expected to be able to provide input to the government in order to overcome population growth and increase plastic waste in Indonesia in this digital era.